Respiratory Microbiota Predicts Clinical Disease Course of Acute Otorrhea in Children With Tympanostomy Tubes. Issue 6 (June 2019) - Man, Wing Ho; van Dongen, Thijs M.A.; Venekamp, Roderick P.; Pluimakers, Vincent G.; Chu, Mei Ling J.N.; van Houten, Marlies A.; Sanders, Elisabeth A.M.; Schilder, Anne G. M.; Bogaert, Debby
Abstract : Background: Acute otitis media (AOM) is one of the most common childhood infections, generally thought to be caused by ascension of bacteria from the nasopharynx (NP) to the middle ear. Using 16S ribosomal RNA–based sequencing, we evaluated the relationship between the NP and middle ear fluid (MEF) microbiota in children with AOM with tympanostomy tubes (AOMT) as a proxy for AOM and explored whether microbiota profiling predicts natural disease course. Methods: Microbiota profiles of paired NP and MEF samples of 94 children below 5 years of age with uncomplicated AOMT were determined. Results: Local diversity ( P < 0.001) and overall microbiota composition ( P < 0.001) of NP and MEF samples differed significantly, although paired NP and MEF samples were much more similar than unpaired samples ( P < 0.001). High qualitative agreement between the presence of individual bacteria in both niches was observed. Abundances of Pseudomonas aeruginosa, Staphylococcus aureus, Streptococcus pyogenes, Turicella otitidis, Klebsiella pneumoniae and Haemophilus spp. were strongly correlated between the 2 niches. Additionally, P. aeruginosa, S. aureus, T. otitidis and Streptococcus pneumoniae abundance in NP were predictive of the presence of a range of oral types of bacteria in MEF. Interestingly, there was no association between Moraxella catarrhalis in NP and MEF samples, which was highly present in NP but virtually absent in MEF. Finally, the NP microbiota composition could predict duration of AOMT, even better than MEF microbiota. Conclusions: We observed substantial correlations between paired NP and MEF microbiota in children with AOMT. Our data also suggest that NP microbiota profiling deserves further exploration as tool for future treatment decisions. Abstract : Supplemental Digital Content is available in the text.